Tài sản thương hiệu thanh long Bình Thuận tiếp cận dưới góc độ người tiêu dùng - Nguyễn Văn Sĩ; Nguyễn Viết Bằng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
This paper defines and measures the impacts of brand equity dimensions of Binh Thuan dragon fruits on the overall brand equity and interactions between these dimensions. A mixed approach is used, including: (i) Qualitative research conducted through direct interviews with experts and focus group discussions, and (ii) quantitative research with two surveys. The results indicate that: (i) brand equity of Binh Thuan dragon fruit is influenced directly by five dimensions, namely brand awareness, brand association, perceived quality, brand loyalty, and perceived safety, and (ii) there exist interactions among these dimensions. Furthermore, perceived quality and perceived safety have most significant effects on the overall brand equity.